Regulatory Diversification of INDEHISCENT in the Capsella Genus Directs Variation in Fruit Morphology - Dong, Yang (Curr Biol, 2019)
Evolution of gene-regulatory sequences is considered the primary driver of morphological variation [1, 2, 3]. In animals, the diversity of body plans between distantly related phyla is due to the differential expression patterns of conserved “toolkit” genes [4]. In plants, variation in expression domains similarly underlie most of the reported diversity of organ shape both in natural evolution and in the domestication of crops [5, 6, 7, 8, 9]. The heart-shaped fruit from members of the Capsella genus is a morphological novelty that has evolved after Capsella diverged from Arabidopsis ∼8 mya [10]. Comparative studies of fruit growth in Capsella and Arabidopsis revealed that the difference in shape is caused by local control of anisotropic growth [11]. Here, we show that sequence variation in regulatory domains of the fruit-tissue identity gene, INDEHISCENT (IND), is responsible for expansion of its expression domain in the heart-shaped fruits from Capsella rubella. We demonstrate that expression of this CrIND gene in the apical part of the valves in Capsella contributes to the heart-shaped appearance. While studies on morphological diversity have revealed the importance of cis-regulatory sequence evolution, few examples exist where the downstream effects of such variation have been characterized in detail. We describe here how CrIND exerts its function on Capsella fruit shape by binding sequence elements of auxin biosynthesis genes to activate their expression and ensure auxin accumulation into highly localized maxima in the fruit valves. Thus, our data provide a direct link between changes in expression pattern and altered hormone homeostasis in the evolution of morphological novelty.